PENGARUH PEMBERIAN DOSIS PUPUK MAJEMUK TERHADAP PERTUMBUHAN TANAMAN SELEDRI (Apium graveolens L.) - Iis Marlina (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2014)
Research on the effect of compound fertilizer on plant growth celery (Apium graveolens L.) has been implemented in October 2014 - February 2015, in plantations 16 Ulu Village, District Seberang Ulu II Palembang. This study aimed to determine the effect of compound fertilizers to celery plant growth and to determine at what dose the average total folium and plant fresh weight. The method used was completely randomized design (CRD), consists of six treatments and four replications. The dose used is A0 (without control), A1 (0.5 grams), A2 (1 gram), A3 (1.5 grams), A4 (2 grams), A5 (2.5 grams). Research results showed that administration of different doses significantly affect of total folium and celery plant fresh weight. The higher the dose applied, the better the plant growth. Best doses indicated in the treatment of A5 (2.5 g), which gives the average total folium 3 (strands) and wet weight of 1.7 grams. Key words: Compound Fertilizer, Apium graveolens L. Growth